A comparison of programmes and services on Mental Fitness for seniors in Austria and Spain - García-Martín, Miguel Ángel; Delgado-Peña, José Jesús; Romo-Parra, María del Carmen; Lang, Gert (My University, 2017)
Developing age-friendly programmes and services focused in Seniors’ Mental Fitness are relevant actions oriented to elder well-being. This paper explores the purposes and methodologies of such implemented programmes and services in Austria and Spain nowadays. The research investigates them in relation to the several aims, namely: 1. What kind of programmes exist which promote active ageing in the light of maintaining and improving mental fitness? 2. What goals are pursued by means of such actions? 3. What methodologies are normally used in them? 4. In which way can they be improved in the light of the previous aims? Using a qualitative case-study design, a representative sample of these actions are analysed by Atlas.ti software from an inductive approach. A constructivist grounded theory approach was used to analyse the data. The information was collected by templates designed ad hoc. Additionally, structured in-depth interviews were held with outstanding providers from some of these actions in order to complement the general information obtained in the former step. These interviews explore aspects of the positive and negative features, as well as improvement proposals for such actions. The results obtained can be applied in the framework of the progress of such programmes and services implementation.
Keywords: Calidad de vida; Ancianos - Protección, asistencia, etc.; Bienestar mental; Personas mayores; Envejecimiento activo